2005
DOI: 10.1007/s11205-004-8021-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Older Adults: Benefits from Caring Services in Hong Kong

Abstract: Many older adults are in need of care. Therefore, older people would generally benefit from the use of caring services, notably including home care, residential care, nursing, and medical services. The contributory factors underlying caring services tend to be a caring perspective that aspires to sustain older people's social relationships and real-life involvement. To gauge the benefits from various social and health services, the present study relies on a large-scale survey of 3000 older adults in Hong Kong,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
(87 reference statements)
0
11
0
1
Order By: Relevance
“…For example, osteoarthritis of the knee has a particularly great impact on the health-related quality of life of Chinese patients (34). …”
Section: Discussionmentioning
confidence: 99%
“…For example, osteoarthritis of the knee has a particularly great impact on the health-related quality of life of Chinese patients (34). …”
Section: Discussionmentioning
confidence: 99%
“…Although a major number of studies are referred to North America population, there are studies that investigate HRQoL of other cultures, too. 58,59,61 In contrast, symptomatic activity and sociodemographic variables such as gender and education, male with higher level of education and inactive disease, showed better HRQoL in patients with inflammatory bowel disease. 48 Additionally, urogenital conditions, hearing impairments, psychiatric disorders, and dermatologic conditions were found to result in relatively favourable functioning.…”
Section: Transplanted Patientsmentioning
confidence: 91%
“…Depression is found to be the most disabling disease and osteoarthritis of the knee had greater impact on the HRQoL than many other chronic diseases, in Chinese patients. 58,59 On the other hand, patients in Europe, who reported the poorest levels of functioning, were those with cerebrovascular/neurologic conditions, renal disease and musculoskeletal conditions, something that raises cross-cultural differences issues. 60 Cross-cultural differences represent the differences between cultures about health and diseases.…”
Section: Transplanted Patientsmentioning
confidence: 99%
“…According to Black and Mindell (1996) and Schoenberg, Coward, and Albrecht (2001), although there is agreement about the benefits of community-based service, there appear to be low rates of use relative to need. Cheung et al (2005) also suggested that care services lack a caring component and infringe on autonomy and decision making by only providing limited choices.…”
Section: Home Care Utilizationmentioning
confidence: 99%
“…For those older adults who have a need, care services are essential for maintaining older adults' physical and mental health (Nolin, Wilburn, Wilburn, & Weaver, 2006). Helping older adults remain in their homes also helps to reduce institutionalization (Cheung, Kwan, Chan, Ngan, Ng, Leung, & Lau, 2005), which can be more costly than providing home care services. Home health care services for older adults are essential to their ability to age in place, as independently as their health will allow.…”
mentioning
confidence: 99%